2007
DOI: 10.1556/aagr.55.2007.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of germination responses of cultivated wheat ( Triticum ) and its wild relative ( Aegilops ) species under salinity, temperature and light

Abstract: The seed germination of bread (Triticum aestivum cv. Bezostaya 1 and Ceyhan 99) and durum (Triticum durum cv. Diyarbakır 81 and Fırat 93) wheat species and their wild relative species (Aegilops biuncialis and Ae. triuncialis) was compared at two light levels, nine NaCl concentrations and three alternating temperature regimes. No seeds germinated at 675 mmol/L NaCl. The highest seed germination (100%) of cultivated wheat cultivars was noted in the control at 15/25°C and 20/30°C, and that of wild wheat species i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Salt resistance in plants is usually quantified in terms of survival rates and/or growing abilities under stress conditions, but it is a complex phenomenon that involves biochemical and physiological processes as well as morphological and developmental changes (Flowers et al. 1977, Greenway and Munns 1980, Yildiz and Kasap 2007). Maize ( Zea mays L.) is considered a moderately salt‐sensitive plant (Maas and Hoffmann 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Salt resistance in plants is usually quantified in terms of survival rates and/or growing abilities under stress conditions, but it is a complex phenomenon that involves biochemical and physiological processes as well as morphological and developmental changes (Flowers et al. 1977, Greenway and Munns 1980, Yildiz and Kasap 2007). Maize ( Zea mays L.) is considered a moderately salt‐sensitive plant (Maas and Hoffmann 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Les travaux de Hervieux et al (2002) ont toutefois été réalisés sur des cultures pures et avec un milieu de culture exempt de fongicide ou de bactéricide, contrairement au nôtre qui contient du bénomyl et de la streptomycine. Il a été démontré qu'au minimum 22 g de NaCl L -1 d'eau dans la solution ajoutée à un papier buvard étaient nécessaires pour inhiber la germination des graines de blé (Yildiz et Kasap 2007); toutefois, à cette concentration, le Bipolaris a été trop affecté pour pouvoir être détecté efficacement. Le NaCl a donc aussi été rejeté comme inhibiteur dans le milieu de détection du B. sorokiniana.…”
Section: Résultats Et Discussion Essais Avec Le Naclunclassified
“…Salt resistance in plants is usually quantified in terms of survival rates [5] and/or growing abilities under stress conditions, involving biochemical and physiological processes as well as morphological and developmental changes [6] , and previous studies [7,8] have indicated that the maintenance of an adequate supply of nutrients to the growth zone should be a key component of the growth response to salinity. Nitrogen fertilization could increase crop yield [9] , and the application of nitrogen fertilizer has also been reported to mitigate significantly the adverse effects caused by high salt stress on a number of plants [10,11] .…”
Section: Introductionmentioning
confidence: 99%